2020
DOI: 10.1111/eci.13265
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and the insulin‐like growth factor system: Implications for colorectal neoplasia

Abstract: Epidemiological studies have strongly associated lower levels of vitamin D and its metabolites with an increased risk of colorectal cancer (CRC). The action of calcitriol, the active metabolite of vitamin D, is mediated by the vitamin D receptor (VDR) that is present in most tissues. In advanced CRC, VDR expression is lowered. Calcitriol has several antineoplastic effects in CRC: it promotes the G1‐phase cycle arrest, lowers vascular endothelial growth factor (VEGF) synthesis and acts on tumour stromal fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In addition, IGF-1 and IGFBP-3 favor angiogenesis by increasing the VEGF gene transcription. An elevated serum ratio for IGF-1/insulin-like growth factor binding protein-3 (IGFBP-3) was associated with increased risk of CRC [ 103 ]. Both IGF-1 and STAT3 can induce CRC development and progression via cell-autonomous and microenvironmental effects [ 82 ].…”
Section: Crc Pathogenesismentioning
confidence: 99%
“…In addition, IGF-1 and IGFBP-3 favor angiogenesis by increasing the VEGF gene transcription. An elevated serum ratio for IGF-1/insulin-like growth factor binding protein-3 (IGFBP-3) was associated with increased risk of CRC [ 103 ]. Both IGF-1 and STAT3 can induce CRC development and progression via cell-autonomous and microenvironmental effects [ 82 ].…”
Section: Crc Pathogenesismentioning
confidence: 99%
“…Among them, the insulin-like growth factor (IGF) plays an important regulatory role in CRC and other malignant tumors, indicating that circRUNX1 can be used as a tumor promoter and is expected to become a potential drug treatment target for CRC. [105][106][107][108][109] In CRC, circPVT1 is upregulated and participates in the proliferation and metastasis of CRC. However, it is noteworthy that overexpression of miR-145 significantly reverses the effect of upregulated circPVT1 on the metastasis of CRC, suggesting that miR-145 is a key downstream effector of circPVT1-mediated CRC metastasis.…”
Section: Cytoplasmmentioning
confidence: 99%
“…12 Besides, another study also indicated that VD 3 increased the expression of IGF-1R . 43 It has been reported that VDR can increase the expression of serum IGF-1. 44 Thus, the IGF-1/IGF-1R pathway might be one of the mediators for VD 3 /VDR signaling, improving intestinal development and function.…”
Section: Discussionmentioning
confidence: 99%